Internal Innovation Capability and ICT Use in the Innovation Process from the View of Connectivity in Japanese SMEs - Hidenori Shigeno; Taisuke Matsuzaki; Masatsugu Tsuji (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2018)
Since new information necessary for innovation mainly comes from outside the firm, it is essential that the firm should innitially obtain such information, and then integrate it with indigenous resources for innovation owned by the firm. During these two processes, it is needless to say that ICT (Information and Communication Technology) has important roles to play. The research questions of this study are to examine how internal innovation capability such as the technological level and R&D (Research and Development), contributes to the innovation and how it is promoted by ICT use. Using the survey data of about 650 SMEs (Small Medium Enterprise) from all over Japan, this study constructs two models with ICT or without ICT and focuses on how SEMs (Structural Equation Modeling) obtain information from external linkages and the role of ICT in the innovation process. SEM is employed to show the causality among factors to promote innovation. The estimation results show that (i) top management is important to promote innovation; (ii) SMEs use two channels to connect to external linkages with and without ICT; and (iii) ICT is the basis of other factors which promote innovation. Keywords: External linkages, SEM, causality, R&D, technology